INFLUENCE OF COMPLEX THERAPY ON ORAL MICROBIOCENOSIS IN PATIENTS WITH CHRONIC HEPATITIS B: A COMPARATIVE APPROACH - Akbarov A.N; Talipova Yu.Sh; Salimov O.R; Tolipova M.A (Western European Studies, 2025)
The aim of this study was to evaluate the effect of complex therapy on the oral microbiological state in patients with chronic hepatitis B (CHB). A comparative analysis was conducted between subgroups of patients receiving complex and traditional therapy. It was found that the application of complex therapy significantly increased the levels of normal flora representatives (Lactobacillus Sp., Veillonella Sp., Streptococcus Sp.) while reducing the counts of opportunistic and pathogenic microorganisms (Staphylococcus Sp., E. coli, Klebsiella Sp., Proteus). In subgroups receiving traditional therapy, positive changes were less pronounced. The obtained results confirm the effectiveness of complex therapy in restoring oral microbiocenosis and reducing the risk of dysbiotic disorders in patients with CHB
Keywords: Chronic hepatitis B; oral microbiota; dysbiosis